Impact of Acupuncture on Chronic Insomnia: A Report of Two Cases with Polysomnographic Evaluation - Sibel Mandıroğlu; Cigdem Ozdilekcan (Medical Association of Pharmacopuncture Institute, 2017)
Objective: This report aimed to present the acupuncture treatment response of two patients who were evaluated with polysomnography. Clinical features: Acupuncture treatment was planned for two patients who refused medical treatment with chronic insomnia. Polysomnographic evaluation was performed at baseline and 1 month after acupuncture treatment. Conclusion: Remarkable improvement was determined in polysomnographic parameters of both cases. After acupuncture treatment, improvements in subjective symptoms such as unrefreshing sleep, morning headache, reduced motivation and daytime performance, tiredness, sleep disturbances, fatigue, and mood worsening in the morning were also observed. Clinical studies with more cases with polysomnographic evaluation are necessary to investigate the effectiveness of acupuncture in the treatment of insomnia.